Characterizing the impacts of vertical transport and photochemical ozone production on an exceedance area. (May 2015) - Yates, Emma L.; Iraci, Laura T.; Austerberry, David; Pierce, R. Bradley; Roby, Matthew C.; Tadić, Jovan M.; Loewenstein, Max; Gore, Warren
Abstract: Offshore and inland vertical profiles of ozone (O3 ) were measured from an aircraft during 16 flights from January 2012 to January 2013 over the northern San Joaquin Valley (SJV) and over the Pacific Ocean. Analysis of in situ measurements presents an assessment of the seasonality and magnitude of net O3 production and transport within the lower troposphere above the SJV. During the high O3 season (May–October), the Dobson Unit sum of O3 in the 0–2 km above sea level (km.a.s.l.) layer above the SJV exceeds that above the offshore profile by up to 20.5%, implying net O3 production over the SJV or vertical transport from above. During extreme events (e.g. Stratosphere-to-troposphere transport) vertical features (areas of enhanced or depleted O3 or water vapor) are observed in the offshore and SJV profiles at different altitudes, demonstrating the scale of vertical mixing during transport. Correlation analysis between offshore O3 profiles and O3 surface sites in the SJV lends further support the hypothesis of vertical mixing. Correlation analysis indicates that O3 mixing ratios at surface sites in the northern and middle SJV show significant correlations to the 1.5–2 km.a.s.l. offshore altitude range. Southern SJV O3 surface sites show a shift towards maximum correlations at increased time-offsets, and O3 surface sites at elevated altitudes show significant correlations with higher offshore altitudes (2.5–4 km.a.s.l.). Highlights: Observation-based analysis of ozone (O3 ) in California and consequences for air quality policy. Assessment of the seasonality of O3 production above California's San Joaquin Valley. Evidence that free tropospheric air affects ground-level O3 . Insights into O3 transport which is difficult to identify by traditional modeling-based approach.